Lama Kontak Dan Peningkatan Kualitas Minyak Jelantah Dengan Masa Bioadsorben Dari Kulit Jeruk Nipis (Citrus aurantifolia S.) - Zulkifli, Arbik (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2023)
This observe aims to determine the impact of bioadsorbent mass from the skin of lime (citrus aurantifolia s) and contact time in improving the best of used cooking oil. This studies became performed using a completely randomized design with two factors, namely: the first factor is the ratio of the weight of bioadorbent to the volume of used cooking oil (A), namely: A1 = 5%, A2 = 10%, A3 = 15%, A4 = 20 %. The second component is the contact time of bioadorbent with used cooking oil (L), namely: L1 = 1 day, L2 = 2 days, L3 = 3 days, L4 = 4 days. The parameters observed were peroxide number, free fatty acid number, water content, color organoleptic. The results of the observe are as follows: The number of lime skin bioadsorbent ratios has a completely significant effect (p 0.01) on peroxide number parameters, free fatty acids, moisture content, and color organoleptics. (p 0.01) in color organoleptic parameters. Giving effect was significantly different (p 0.05) on the parameters of free fatty acids. And it was not significantly different (p 0.05) in peroxide number parameters, and water content.